Acoustic performance enhancement in a railway passenger carriage using hybrid ray-tracing and image-source method. (15th December 2020) - Panahi, Emad; Younesian, Davood
Abstract: Geometry of cabins, corridors, and materials used in railway passenger carriages can play important roles in acoustic performance inside the rail cars. In order to evaluate the noise level inside a rail car, a hybrid method based on the ray-tracing and image-source techniques is employed. A parametric model is constructed based on the field experiment performed in a typical coach cabin namely Fadak train in Iranian Railway. An Omni-directional sound source inside the passenger carriage is employed inside the cabin once for an unequipped cabin and once for operational one. Acoustic parameters such as reverberation time (T30), Center time (Ts), and the sound pressure level have been calculated and results are validated with experimental acoustic measurements. The model is experimentally calibrated and then acoustics performance of the passenger coach is enhanced by modifying the materials and absorption coefficients against two dominant sound sources in low to middle speed ranges. It is found the simple recommendation can remarkably enhance the acoustic performance over a broad range of frequencies.